Manajemen Kurikulum Takhassus Tafsir Wa Ulumuhu dalam Mencetak Ahli Tafsir yang Wasathiyah (Studi Pada Ma’had Aly Nurul Qadim Probolinggo - Syaiful Anam; Agus Supriyadi; Agus Angga Rizky; Ummi Habibatul Islamiyah (Cyber Media Indonesia, 2024)
Ma’had Aly Nurul Qadim is an educational institution with a noble vision and mission to produce a generation of moderate interpretations. This vision is driven by the increasing violence in the name of religious understanding, which, if left unchecked, can damage the unity and brotherhood that has long been fostered in this country. Therefore, it is essential to have educational institutions capable of producing moderate cadre of interpretation. This study aims to analyze the management of the Tafsir Wa Ulumuhu curriculum at Ma’had Aly Nurul Qadim with a focus on: 1) Analyzing the planning of the Takhassus Tafsir Wa Ulumuhu curriculum, 2) Analyzing the implementation of the Takhassus Tafsir Wa Ulumuhu curriculum, and 3) Analyzing the challenges in managing the Takhassus Tafsir Wa Ulumuhu curriculum. This research employs a qualitative approach with a case study design. Data collection was conducted through interviews, observations, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. Data validity was checked using source and method triangulation. The research informants were the director (mudir) of Ma’had Aly, the deputy director (naib mudir), lecturers, and students. The results of the study indicate that: 1) The planning of the Takhassus Tafsir Wa Ulumuhu curriculum at Ma’had Aly Nurul Qadim involves formulating the characteristics of desired tafsir experts, graduate profiles, objectives, as well as the vision and mission. 2) The implementation of the Tafsir Wa Ulumuhu curriculum at Ma’had Aly Nurul Qadim begins with the recruitment of prospective students, using a student-centered learning approach. Commonly used methods include discussions, assignments, and regular bahtsul masail (problem-solving sessions). The graduation system includes Qiraatul Kutub tests, memorization of one juz of the Qur'an each semester, and comprehension of classical texts. Additionally, students are housed in dormitories, national seminars are held, and community service activities are conducted. 3) Internal challenges faced by Ma’had Aly Nurul Qadim in implementing the Tafsir Wa Ulumuhu curriculum include student input and human resources (both structural and teaching staff). External challenges include library and computer lab facilities. Abstrak Ma’had Aly Nurul Qadim merupakan salah satu lembaga pendidikan yang memiliki visi dan misi mulia untuk mencetak generasi ahli tafsir yang moderat. Visi ini diusung karena maraknya kekerasan yang mengatasnamakan pemahaman agama, yang jika dibiarkan, dapat merusak persatuan dan persaudaraan yang telah lama terjalin di negara ini. Oleh karena itu, diperlukan lembaga pendidikan yang mampu menghasilkan kader tafsir yang moderat. Penelitian ini bertujuan untuk menganalisis manajemen kurikulum Tafsir Wa Ulumuhu di Ma’had Aly Nurul Qadim dengan sub fokus: 1) Menganalisis perencanaan (planning) kurikulum Takhassus Tafsir Wa Ulumuhu, 2) Menganalisis pelaksanaan (actuating) kurikulum Takhassus Tafsir Wa Ulumuhu, dan 3) Menganalisis kendala manajemen kurikulum Takhassus Tafsir Wa Ulumuhu. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi kasus. Pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi. Teknik analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diperiksa menggunakan teknik triangulasi sumber dan metode. Informan penelitian adalah mudir Ma’had Aly, naib mudir, dosen, dan mahasantri. Hasil penelitian menunjukkan bahwa: 1) Perencanaan kurikulum Takhassus Tafsir Wa Ulumuhu di Ma’had Aly Nurul Qadim dilakukan dengan merumuskan ciri-ciri ahli tafsir yang diinginkan, profil lulusan, tujuan, serta visi dan misi. 2) Pelaksanaan kurikulum Tafsir Wa Ulumuhu di Ma’had Aly Nurul Qadim dimulai dengan perekrutan calon mahasantri, menggunakan pendekatan pembelajaran berbasis murid, dan metode yang sering digunakan adalah diskusi, penugasan, dan kegiatan bahtsul masail. Sistem kelulusan meliputi Tes Qiraatul Kutub, hafalan 1 juz al-Qur’an setiap semester, dan pemahaman kitab. Selain itu, mahasantri diasramakan, diadakan seminar kebangsaan, dan pengabdian kepada masyarakat. 3) Kendala internal yang dihadapi Ma’had Aly Nurul Qadim dalam mengimplementasikan kurikulum Tafsir Wa Ulumuhu adalah input mahasantri dan sumber daya manusia (struktural dan dosen). Kendala eksternal meliputi sarana perpustakaan dan laboratorium komputer.